2001
DOI: 10.1359/jbmr.2001.16.11.2152
|View full text |Cite
|
Sign up to set email alerts
|

Five-Week Intake of Short-Chain Fructo-Oligosaccharides Increases Intestinal Absorption and Status of Magnesium in Postmenopausal Women

Abstract: Fermentable carbohydrates have been shown to be nondigestible by human enzymes in the small intestine but are fermented extensively in the large bowel to short-chain fatty acids (SCFAs), which can increase mineral absorption. It has been shown that feeding such carbohydrates including short-chain fructo-oligosaccharides

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
1
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(62 citation statements)
references
References 37 publications
3
56
1
2
Order By: Relevance
“…In postmenopausal women (50-70 aged) Tahiri et al (2001) have shown not signifi cant changes of bone turnover after 5 weeks scFOS treatment, but, a trend towards a higher activity was observed in women within less than 7 years of menopause. Concerning bone resorption, both pro-and prebiotics were associated with improvement of DPD values and in early postmenopausal women, the effect of sc-FOS was even intensified.…”
Section: Discussionmentioning
confidence: 86%
“…In postmenopausal women (50-70 aged) Tahiri et al (2001) have shown not signifi cant changes of bone turnover after 5 weeks scFOS treatment, but, a trend towards a higher activity was observed in women within less than 7 years of menopause. Concerning bone resorption, both pro-and prebiotics were associated with improvement of DPD values and in early postmenopausal women, the effect of sc-FOS was even intensified.…”
Section: Discussionmentioning
confidence: 86%
“…In postmenopausal women fructooligosaccharides increased magnesium absorption and status after five weeks (Tahiri et al, 2001). However, when women were stratified by time of postmenopause, a trend was observed (P < 0,1) of a beneficial effect of short-chain oligofructose on calcium balance in women >6 years postmenopause but not in women <6 years postmenopause (Tahiri et al, 2003).…”
Section: Increased Mineral Absorptionmentioning
confidence: 88%
“…There are several proposed explanations for the beneficial effect of inulin-type fructans on mineral absorption and bioavailability, i.e., a higher water content in the large intestine due to an osmotic effect, acidification of the cecal contents and increased solubility in intestinal lumen by short-chain fatty acids (SCFA), and greater absorptive surface due to hypertrophy of the mucosa (Tahiri et al, 2001;Roberfroid, 2005b;Rondón et al, 2008b).…”
Section: Discussionmentioning
confidence: 99%